Gender Differences, Risk and Probability Weights in Financial Decisions - Loo , Angie Yi Zhen; Yu , Ting; Kean , Siang Ch′ng (School of Social Sciences, 2015)
Numerous studies have shown that decision makers do not usually treat probabilities linearly. Instead, people tend to overweight small probabilities and underweight large probabilities. The purpose of this research is to investigate whether women weigh probabilities differently than men. Besides that, this research also aims to examine whether women exhibit greater financial risk aversion than men. Women are commonly stereotyped as more risk averse than men in financial decision making. To examine some of the beliefs and preferences that underlie this difference, a stratified sample of 289 working adults (144 males and 145 females) aged 20–54 were interviewed within randomly selected geographical area across Penang Island. With this field experiment, we wish to generate a more credible and accurate results as compared to previous studies that used students as their subjects. This study confirmed the findings of previous researches that men and women differ in their financial decisions. In the gain domains, men tend to overweight smaller probabilities more than women (risk seeking) and women tend to underweight larger probabilities more than men (risk averse). While in the loss domains, when the probabilities were small, women were risk averse because they tend to overweight smaller probabilities more than men. When the probability became larger, women were exhibited as risk seeking as men because both of them perceived to have low chance of losing